Analisis Kinerja Pegawai Pada Bidang Kesejahteraan Rakyat dan Perekonomian Dalam Upaya Penyaluran Program Keluarga Miskin di Kelurahan Menanggal Kota Surabaya - Ramadyna, Noza Fawwas; Oktariyanda, Trenda Aktiva (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze employee performance in the Division of Public Welfare and Economy in the implementation of the Poor Family Program in Menanggal Subdistrict, Surabaya City. A qualitative approach was used with four main performance indicators: the need for achievement, the need for power, compensation, and leadership policies. The results show that employees demonstrate strong motivation in carrying out their duties, particularly in ensuring that social assistance reaches those truly in need. However, challenges persist, including limited resources and weak coordination between village officials and neighborhood leaders (RT/RW), leading to inaccuracies in beneficiary targeting. The need for power is reflected in the employees’ involvement in decision-making and providing guidance to citizens, although these efforts are not always supported by accurate data. Compensation, especially for non-permanent staff, is still considered insufficient, affecting work morale and productivity. Leadership policies arrelatively supportive of efficient workflows, yet improvements are needed in updating beneficiary data and monitoring program implementation. Other challenges include community dependence on social assistance and low public awareness of eligibility procedures and criteria. The study suggests the need for enhanced staff training, stronger cross-sector coordination, and the integration of empowerment programs to ensure that assistance not only serves immediate needs but also encourages long-term economic self-reliance among beneficiaries.